Accurate inferences of others' thoughts depend on where they stand on the empathic trait continuum. (1st October 2019) - Wu, Wenjie; Mitchell, Peter
Abstract: This research explores the possibility that a person's (perceiver's) prospects of making a correct inference of another person's (target's) inner states depends on the personal characteristics of the target, potentially relating to how readable they are. Twenty-seven targets completed the Empathy Quotient (EQ) and were classified as having low, average or high EQ. They were unobtrusively videoed while thinking of an event of happiness, gratitude, anger and sadness. After observing targets thinking of such a past event, fifty-two perceivers (participants) in Study 1 were asked to infer what the target was thinking, and fifty perceivers in Study 2 were asked to rate the target's expression – positive or negative. Results suggested that (1) perceivers' accuracy in detecting targets' thoughts depended on which EQ group the target belonged to, and (2) target readability is not a proxy measure for level of target expressiveness. In other words, something about EQ status renders targets more or less easy to read in a way that is not simply explained by expressive people being more readable. We conclude with discussion of the importance of the target's trait as well as situation they experience in determining how accurately a perceiver might infer their inner states.